2017
DOI: 10.1371/journal.pone.0188743
|View full text |Cite
|
Sign up to set email alerts
|

Magnification of digital hip radiographs differs between clinical workplaces

Abstract: Preoperative planning for total hip arthroplasty includes templating on anteroposterior radiographs. It is necessary to consider radiographic magnification in order to scale templates accurately. Studies dealing with hip templating report different values of radiographic magnification. It is not clear if the observed difference in magnification between the studies is caused by variability in studied groups, methodology or instrumentation. We hypothesize that there is a difference in magnification between clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Within the literature there is a preference for the use of fixed MF. 6,10,12,[17][18][19] However our results suggest that fixed MF values of 110-120% could be too low for accurate templating. To our knowledge, studies that prefer the use of a fixed MF have neglected to mention the effect of patient body habitus.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Within the literature there is a preference for the use of fixed MF. 6,10,12,[17][18][19] However our results suggest that fixed MF values of 110-120% could be too low for accurate templating. To our knowledge, studies that prefer the use of a fixed MF have neglected to mention the effect of patient body habitus.…”
Section: Discussionmentioning
confidence: 66%
“…5,6,11,18,20,22 As shown in our results the use of a SID of 100 cm concurred the greatest degree of magnification on the image and caused the greatest shift from the typical fixed MF value of 110% to 120%. Hornová et al 12 and Olmedo-Garcia et al 20 suggested that standardised MF should be calibrated for each clinical site based upon individual protocols to account for this discrepancy in SID. Kwok et al, 14 calculated the degree of magnification in a series of images, ensuring that SID and SOD were included on the initial radiographs by the radiographer as part of their inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two other similar studies using the implanted femoral head have both shown magnification error to consistently near 6%, which suggests despite a standardized radiological protocol, scaling using an ECM has inherent consistent magnification error of 6% [13,19]. Magnification error can also differ between different radiological departments which use the same standardized protocol [20].…”
Section: Discussionmentioning
confidence: 98%